Pengaruh Pembangunan Jembatan Cirahong terhadap Perkembangan Perkebunan di Kabupaten Galuh-Ciamis 1893-1942 - Ami Abdullah Fahmi; Ramdhan Prasetyo (Diakronika, 2022)
The writing of this article started from the author's interest in Dutch heritage buildings around the Tasikmalaya area, which still stand strong today. One of the most interesting is the Cirahong Bridge. This bridge was built during the colonial period as a means of transportation. According to the blueprint, the Cirahong bridge is the only multifunctional bridge in Indonesia because the upper part is used for the train line, while the lower part is used for connecting cars and motorbikes from Manonjaya to Ciamis. The construction of this bridge is also interesting because it involves several political lobbies from the Galuh rulers (ciamis) who want to change the train line from its original direction towards Cimaragas to Ciamis. This lobby bears sweet fruit with the change of route to Ciamis. This study aims to determine the development of the Cirahong railway bridge and its impact on the development of plantations in the Galuh-Ciamis Regency. This article uses the Historical Method, which includes the stages of heuristics, criticism, interpretation, and historiography. The construction of the Cirahong Bridge, which began in 1893, took seven months in the manufacturing process. The construction of this bridge was a must after the Bogor-Cilacap railway line switched from Cimaragas to Ciamis as a result of political lobbying from RAA Kusumadiningrat. This political lobby bore fruit for Galuh because it had a direct impact on Galuh's economy, marked by the construction of 39 new plantations and the emergence of many new jobs related to rail transportation facilities in Galuh due to the existence of a train line passing through Galuh.